BANCOS DE ALIMENTOS PARANAENSES E O COMBATE ÀS PERDAS E DESPERDÍCIOS DE ALIMENTOS NA PERSPECTIVA DA TRANSIÇÃO SOCIOTÉCNICA PARA A SUSTENTABILIDADE - KUASOSKI, MARLI (2022)
Transition theory has been studied in the context of sustainability in several systems, including the food system, which presents a paradox: on the one hand, a significant amount of food waste; on the other, a portion of the population experiencing food and nutrition insecurity. Food banks are important mechanisms to deter food waste and hunger, balancing the environmental, social, and economic pillars. Moreover, they help to reduce hunger, promote social justice, and cut down food residues and their environmental impacts, thus decreasing the financial resources spent on food production and logistics. This study's purpose is to understand how public and private food banks in Paraná contribute to reducing food loss and waste under the lens of sustainability transitions. This study is descriptive-exploratory, bibliographic, documentary, and multi-case, with a qualitative approach. The results indicated that food banks are conducive spaces for developing ideas, experiences, knowledge, and skills that contribute to reducing food waste and food and nutrition insecurity, which help in achieving a sustainable food system. Donors and beneficiaries are the main actors, forming a cooperation network that results in more donations. The socio-technical regime is favorable for the development of food banks, although it has limitations related to infrastructure, culture, financial resources, policies, scientific knowledge, and technology, all being challenges to be faced. The socio-technical landscape influences the regime toward less waste because of the global debates on food culture, climate change, food and nutrition insecurity, war, and Covid-19. These factors point to the need for changes in cultural patterns about food, favoring the role played by food banks, which have demonstrated innovative practices to increase donations during the pandemic and methods to reuse food. However, the food banks investigated are in the phase of technological improvement, which reveals the need for greater development in these entities so they can compete in a more sustainable regime. Furthermore, food banks in Paraná will only be able to boost this transition with deeper changes, especially in the food culture of a society that still tends to waste. Changes in the entire food production chain will also be necessary, from production to consumption. Finally, the foremost contribution of this thesis lies in the proposal of an analytical framework from a multilevel perspective so that food banks can improve the interrelationships between actors, manage aspects related to the niche, and better articulate their actions with the socio-technical regime. Thus, it is desirable that public food banks have a system to track donated food, more volunteering, an expanded network of relationships, further technical-scientific research, and a stronger link with the actors of the socio-technical food regime. For future research, we suggest comparing the results with investigations of food banks in other Brazilian states and even other countries. Moreover, other studies could be developed in niches similar to food banks.